The Association of Robotic-Assisted Vasectomy Reversal with Improved Surgical Ergonomics and Clinical Outcomes: A Systematic Review - Ade Juanda; Ahlan Syahreza (The International Journal of Medical Science and Health Research, 2026)
Introduction: Vasectomy reversal (VR) is a technically demanding microsurgical procedure. While microsurgical vasectomy reversal (MVR) is the established gold standard, it presents significant ergonomic challenges and a steep learning curve for surgeons. Robot-assisted vasectomy reversal (RAVR) has emerged as a technological evolution aimed at mitigating these challenges. This systematic review aims to critically evaluate the association of RAVR with surgical ergonomics and clinical outcomes compared to MVR. Methods: A systematic literature search was conducted across PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library databases in adherence with PRISMA guidelines. Studies directly comparing clinical, operative, and ergonomic outcomes of RAVR versus MVR in human subjects were included. Key outcomes of interest included patency rates, pregnancy rates, operative times, complication rates, and quantitative ergonomic assessments. The methodological quality of included studies was assessed using the Cochrane Risk of Bias tool for randomized trials and the Newcastle-Ottawa Scale for non-randomized studies. Results: Seventeen comparative studies and relevant supporting literature were included. The analysis revealed that RAVR is associated with pooled patency rates that are comparable or superior to MVR (94.4% vs. 87.5% in one meta-analysis). Pregnancy rates appeared similar, though long-term data for RAVR is less mature. Operative times for RAVR were found to be shorter than MVR after an initial learning curve of approximately 75 cases. Most notably, the evidence consistently demonstrated significant ergonomic advantages for RAVR, including the elimination of physiological tremor, reduced surgeon muscle fatigue as measured by electromyography, and improved postural comfort. Complication rates were low and comparable between both techniques. Discussion: The integration of robotic technology addresses the core ergonomic limitations of conventional microsurgery. The reduction in physical strain and tremor filtration may directly contribute to a more precise and stable anastomosis, potentially improving long-term patency. While the clinical efficacy of RAVR is at least non-inferior to the gold standard, its primary advantage lies in enhancing the surgeon's performance and comfort. This may also facilitate a less arduous learning curve, potentially broadening the accessibility of high-quality vasectomy reversal. Conclusion: RAVR is a safe, feasible, and effective alternative to MVR. It offers significant, quantifiable ergonomic benefits to the surgeon while achieving excellent clinical outcomes that are non-inferior, and in some metrics potentially superior, to the conventional microsurgical approach. Future large-scale, multicenter randomized controlled trials are warranted to definitively establish long-term pregnancy outcomes and cost-effectiveness.